Gaze as a Disruption of Image. Between Mimesis and Mimicry - Siegert, Bernhard (Iluminace, 2011)
A theoretical-philosophical essay on mediality and its history, not so much concerned with the media object itself, but rather with the genesis and nature of the media environment as a framework for media operations and material objects.
Keywords: media; evolution of media; film science and research; film theory